Reducing Community Participation in the Preparation of Environmental Impact Assessments (EIA): Evidence from Indonesia - Broto Laksito, FX Hastowo; Bawono , Aji; Ikrimah , Afridah (CV. Ius et Ambientis, 2024)
Globalisation compels nations to adapt to contemporary advancements, including enhancing economic growth through policies designed to attract investment from diverse foreign enterprises. Legal instruments should not be viewed solely as tools that cater to human interests; instead, they serve as mechanisms for community development to ensure the survival of humans, the environment, and other living organisms by the principles of sustainable development encompassing economic, social, and environmental considerations. This research examines favourable legislative restrictions in Indonesia that diminish community engagement in formulating Environmental Impact Assessments, potentially exacerbating environmental degradation. The findings indicate that modifications in regulatory standards within the Job Creation Law about the environmental sector, compared to the Environmental Protection and Management Law, have diminished the involvement of environmental observers in formulating Environmental Impact Assessments, now solely acknowledging affected communities. Members of the environmentalist community play a vital role in evaluating the implications of a company's actions, which is essential for preserving environmental sustainability and promoting sustainable development. The article's conclusion highlights policymakers' and lawmakers' need to comprehend the law's significance in attaining sustainable development objectives. The diminished role of community involvement in preparing Environmental Impact Assessments, which possess greater insight into potential environmental harm, signifies a deterioration in democracy in Indonesia.